Saproksyliczne skoczogonki (Collembola) Wigierskiego Parku Narodowego - Skarżyński, Dariusz; Krzysztofiak, Anna; Piwnik, Agata (Leśne Prace Badawcze, 2016)
Faunistic and ecological studies on saproxylic Collembola species were carried out in the Wigry National Park (NE Poland). Nine sites representing Tilio-Carpinetum , Serratulo-Pinetum and Peucedano-Pinetum habitats each including three different levels of disturbance were visited twice in 2015. Samples from fallen logs in different stages of decay, neighboring litter and soil as well as arboreal epiphytes were taken on each visit. The Collembola specimens were then extracted using Tullgren funnels resulting in a total of 73 838 specimens from 270 samples. Specimen identification revealed the occurrence of 63 species, including 5 saproxylobiontic, 7 saproxylophilous, 4 xerophilous species living in epiphytic mosses and lichens as well as 47 hemiedaphic or euedaphic species. This composition of saproxylic fauna seems to be typical for the region with the most diverse assemblages being found in Tilio-Carpinetum habitats, while Serratulo-Pinetum and Peucedano-Pinetum are clearly less diverse. Additionally, a slight decrease in the number of Collembola species with increasing forest disturbance was observed. Furthermore, an increase in the number of Collembola species with the degree of dead wood decomposition was also found. This indicates that saproxylic springtail assemblages are sensitive to anthropogenic changes.